Answer:
Step-by-step explanation:
a) Standard Form is ...
Ax + By = C
where A > 0 and A, B, C are mutually prime.
To get that form, we can add 2x-5 to both sides of the equation:
(2x -5) -2x = (2x -5) -y +5
-5 = 2x -y
Then we can swap sides of the equal sign:
2x -y = -5 . . . . . . standard form
Matching this to the generic standard form equation, we find ...
A = 2
B = -1
C = -5
__
b) We can solve for y by adding 2x+y to both sides of the equation:
(2x +y) -2x = (2x +y) -y +5
y = 2x +5 . . . . . . slope-intercept form